(untitled) - Block, Jay A. (New York, NY, 2004)
Great Answers! Great Questions! For Your Job Interview prepares readers for anything that might come their way during that allimportant interview. This thorough guide provides answers for all the most common questions interviewers ask, and suggests smart questions human resources professionals like to hear in return. This comprehensive interview game plan features: 101 answers to any tough question, 101 questions that showcase the job hunter's intelligence and skills,Practical strategies for online job searching and expert advice on telephone interviews, physical presentation, following up the interview, and salary negotiation.
Keywords: Employment interviewing